Effect of velocity and added resistance on kinematical and kinetical parameters in front crawl - Schnitzler, C.; Brazier, T.; Button, C.; Chollet, D. (1st International Scientific Conference of Aquatic Space Activities, 2008)
The effect of increasing velocity and adding resistance on kinematical and kinetical parameters during the stroke cycle was examined in front crawl for 7 national level swimmers. In a flume, 3 drag conditions provided by a resistance parachute (PA) were tested at 5 velocities. Video footage and force sensors were used to measure the spatio-temporal coordination and force parameters. The results showed that an increase in velocity (V) led to increases in stroke rate (SR), Index of coordination (IdC), and a non significant change in force impulse per cycle, whatever the condition. In PA conditions, significant increases in the IdC, force impulse, and a decrease in SR were recorded (p<0.05). These results show that in normal conditions swimmers adapt to a change in velocity by modifying kinematics rather than kinetical parameters, whereas in PA conditions there is an enhancement of both of the parameters.